Development and Application of Starter Cultures (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This Special Issue explores the evolving field of starter cultures, essential for improving raw material processing and the production of fermented foods. As industrial food production grows, the need for effective fermentation solutions becomes critical. This collection highlights two primary approaches for developing starter cultures: using well-defined species and strains for consistency and standardization or replicating biodiverse, autochthonous natural cultures to preserve unique sensory qualities and local microbial diversity. While selected starters offer ease of use and industrial scalability, natural starters maintain the distinctive flavors tied to their place of origin. This Special Issue gathers innovative research aimed at creating starter cultures that balance safety, quality, and biodiversity preservation, applicable to artisanal, pilot, and industrial production scales.